(untitled) (Ameghiniana, 2013)
A discovery is mentioned of a varied and abundant fauna of Conodonts found in limestone samples of the San Juan Formation, outcropping in the northern region of Departamento Jachal, San Juan Province, near the boundary with La Rioja Province. These limestones also bear a macrofauna with Nautiloidea. This interesting Conodont fauna is summarily described in a preliminar way. Hitherto 8 genera and 12 species have been identified in it. The generic association is proper for the Middle Ordovician in North America and Europe.